THE RELATIONSHIP BETWEEN STRESS LEVELS AND THE FREQUENCY OF BREAST MILK PRODUCTION SMOOTHNESS AMONG BREASTFEEDING MOTHERS IN THE NICU ROOM OF RSU BUNDA PADANG - Amira Esti; Yohana Suganda; Elwitri Silvia; Septa Nely; Desi Asra Syafril (Ensiklopedia Research and Community Service Review, 2026)
Abstract: Breast milk is the best source of nutrition for infants and plays an essential role in supporting infant growth and development. Mothers whose babies are admitted to the Neonatal Intensive Care Unit (NICU) often experience stress due to their infants’ health conditions, the intensive care environment, and limited interaction with their babies. This study aimed to determine the relationship between stress levels and the frequency of breast milk production smoothness among breastfeeding mothers in the NICU Room of RSU Bunda Padang in 2026. This study employed a quantitative research method with a correlational analytic design using a cross-sectional approach. The research was conducted in the NICU Room of RSU Bunda Padang from April 28 to May 29, 2026. The study population consisted of 80 respondents, with a sample of 67 respondents selected using a purposive sampling technique. Data were collected using the Depression Anxiety Stress Scales (DASS-42) questionnaire to measure stress levels and a breast milk production smoothness questionnaire. Data were analyzed using the Chi-Square test with a significance level of α = 0.05. The results showed that more than half of the respondents experienced moderate stress, accounting for 36 respondents (53.7%), while 31 respondents (46.3%) experienced mild stress. Regarding breast milk production smoothness, 35 respondents (52.2%) experienced smooth breast milk production, whereas 32 respondents (47.8%) experienced less smooth breast milk production. The bivariate analysis revealed that all respondents who experienced less smooth breast milk production were in the moderate stress category (100%). The Chi-Square test yielded a p-value of 0.000 (p ≤ 0.05), indicating a significant relationship between stress levels and the frequency of breast milk production smoothness among breastfeeding mothers in the NICU Room of RSU Bunda Padang in 2026.Keywords: Stress Level, Breast Milk Production, Breast Milk Production Smoothness, Breastfeeding Mothers, NICU.